Design of a wideband Y‐shaped antenna for the application in IoT and 5G communication. (28th October 2021) - Mukherjee, Kaushal; Mukhopadhyay, Subhadeep; Roy, Sahadev
Summary: A small wideband Y‐shaped antenna is presented in this paper. A monopole of Y‐shaped with two rectangular‐shape frequency shifting strip is used to produce a compact dimension of 10 mm × 12 mm on a 1‐mm‐thick FR4 substrate. The antenna has an impedance bandwidth (measured below −10 dB from 39.57 to 44.63 GHz), a gain more than 4.9 dB, radiation efficiency of 81%, and voltage standing wave ratio (VSWR) < 2, within the bandwidth of interest, making it a viable option for 5G applications. The use of a (01.7850 × 2.6775 × 00.02) mm 3 metallic strip located above the feed line is also shown to efficiently increase the antenna bandwidth to values greater than 5 GHz without affecting the other antenna parameters. Additionally, the measured results in comparison with the simulated results reveal negligible changes, confirming that the proposed antenna is also suitable for the applications of 5G with Internet of Things. Abstract : The proposed antenna has a miniaturized size (10 × 12 × 1) mm 3, operational Bandwidth of 5.06 GHz, peak gain of 4.93 dB, radiation efficiency of 81%, and VSWR < 2. The designed antenna covers four major 5G licensed bands, as follows: n257, n258, n259, and n260. Additionally, the measured results in comparison with the simulated results reveal negligible changes, confirming that the proposed antenna is also suitable for the applications of 5G with Internet of Things.